Giving birth to a new approach: a retrospective comparison of radiation safety parameters between transradial and transfemoral approaches for uterine fibroid embolization at Groote Schuur Hospital, South Africa - Kassim, Jateel (Division of Radiology, 2025)
Background: Uterine artery embolisation (UAE) is a recognised minimally invasive, effective and fertility preserving treatment option for patients with symptomatic uterine leiomyomas. The conventional transfemoral access (TFA) in UAEs remains the method of choice for the majority of South African interventional radiologists. Transradial access (TRA) has grown as a viable alternate vascular access. The advantages of TRA over TFA have been well documented, however a lack of safety parameter comparison in procedures performed via TRA versus TFA remains. Objectives: To compare the mean radiation dose and accumulative fluoroscopy time between TRA and TFA UAEs performed for the treatment of uterine leiomyomas. Method A single-institution retrospective study was conducted on all female patients having undergone UAE for symptomatic uterine leiomyomas at GSH between 1 January 2018 and 31 March 2020. Safety parameters between TFA and TRA UAEs were compared. Results Of the 61 patients having undergone UAEs, 29 were TFA and 32 TRA UAEs. No statistical difference was observed between the procedural and screening times, however there was a statistically significant difference for mean radiation dose: TFA recorded a mean radiation dose of 1 158 (95% CI 721- 1596), TRA had a mean of 639 (95% CI 36-1243 units) higher than TFA (p-value = 0.038). Conclusion: The comparison of the majority of the safety parameters between TRA and TFA UAEs in our study demonstrated no statistical significance. The increase in radiation dose in the TRA vs TFA group is comparable to other studies and although statistically significant, is small. Therefore, TRA still forms a safe viable alternate form of access for UAEs